17=c-(-7)

Simple and best practice solution for 17=c-(-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17=c-(-7) equation:


Simplifying
17 = c + -1(-7)

Multiply -1 * -7
17 = c + 7

Reorder the terms:
17 = 7 + c

Solving
17 = 7 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
17 + -1c = 7 + c + -1c

Combine like terms: c + -1c = 0
17 + -1c = 7 + 0
17 + -1c = 7

Add '-17' to each side of the equation.
17 + -17 + -1c = 7 + -17

Combine like terms: 17 + -17 = 0
0 + -1c = 7 + -17
-1c = 7 + -17

Combine like terms: 7 + -17 = -10
-1c = -10

Divide each side by '-1'.
c = 10

Simplifying
c = 10

See similar equations:

| 6n^2+29n+28=0 | | 3Cosx=3 | | 12=-4g | | 6x-10-4x+13=-2 | | 15=s-(-4) | | 16-10/2 | | 9n^2+36n+20=0 | | a*6-1=10 | | 1,430/2=t/5 | | b-(-55)=62 | | 3/4x-1/3x=1/12 | | 5x+5+7x-8+4x-13+5x-2=360 | | 6c=-78 | | 5x-13=4x+5 | | 10=16 | | -3(2-3y)=2(1+5y) | | v/2 | | a^3c^2/9b | | x+4=10x-14 | | 4(3x+1)=5x+66 | | .5x+12.3=7.1-1.1x | | 28=3X-14 | | 4(x+x+7)-2x+8-4= | | T^3+8t^2+15t=0 | | 2X^2-7X+3=5 | | (-3-1/3x)^3 | | 2+0.5d=25 | | h=3+80t-16t^2 | | x^2+9=103 | | 5k-21=-3k+24 | | 0.5d-2=25 | | -16p+13p+-1=14 |

Equations solver categories